Polyimide composite aerogels towards highly efficient microwave absorption and thermal insulation. (October 2022) - Li, Jiaqiang; Zhang, Ling; Pang, Yucen; Wang, Xue; Bai, Ben; Zhang, Wenting; Luo, Chuyang; Liu, Wanshuang; Zhang, Liying
Abstract: The development of lightweight microwave absorbing materials with thermal insulation is critical to the aerospace industry. In this work, polyimide (PI) composite aerogels with efficient microwave absorption and thermal insulation performance were fabricated with the addition of amino-functionalized core–shell structure ferroferric oxide (NH2 -SiO2 @Fe3 O4 ) via an eco-friendly freeze-drying method followed by a thermal imidization process. PI works as the skeleton, where NH2 -SiO2 @Fe3 O4 nanoparticles not only serve as microwave absorbers but also can induce interfacial thermal resistance, resulting in improved thermal insulation performance. Herein, the strong reflection loss ( RL ) reaches −49.7 dB at 14.0 GHz and an effective absorption bandwidth ( EAB ) of 10.0 GHz (7.2–16.4 GHz, 17.2–18.0 GHz) is achieved. Additionally, the PI composite aerogel shows superior thermal insulation with a thermal conductivity of 44.7 mW/(m·k). This study may offer a promising approach to develop PI composite aerogels with integrated microwave absorption and thermal insulation functions.